Quantitative MS-based enzymology of caspases reveals distinct protein substrate specificities, hierarchies, and cellular roles - Julien, Olivier (Proc Natl Acad Sci U S A, 2016)
Proteases constitute the largest enzyme family, yet their biological roles are obscured by our rudimentary understanding of their cellular substrates. There are 12 human caspases that play crucial roles in inflammation and cell differentiation and drive the terminal stages of cell death. Recent N-terminomics technologies have begun to enumerate the diverse substrates individual caspases can cleave in complex cell lysates. It is clear that many caspases have shared substrates; however, few data exist about the catalytic efficiencies (k(cat)/K(M)) of these substrates, which is critical to understanding their true substrate preferences. In this study, we use quantitative MS to determine the catalytic efficiencies for hundreds of natural protease substrates in cellular lysate for two understudied members: caspase-2 and caspase-6. Most substrates are new, and the cleavage rates vary up to 500-fold. We compare the cleavage rates for common substrates with those found for caspase-3, caspase-7, and caspase-8, involved in apoptosis. There is little correlation in catalytic efficiencies among the five caspases, suggesting each has a unique set of preferred substrates, and thus more specialized roles than previously understood. We synthesized peptide substrates on the basis of protein cleavage sites and found similar catalytic efficiencies between the protein and peptide substrates. These data suggest the rates of proteolysis are dominated more by local primary sequence, and less by the tertiary protein fold. Our studies highlight that global quantitative rate analysis for posttranslational modification enzymes in complex milieus for native substrates is critical to better define their functions and relative sequence of events.